Potential Use of Stem Cells for Kidney Regeneration - Takashi Yokoo; Kei Matsumoto; Shinya Yokote (International Journal of Nephrology)
Significant advances have been made in stem cell research over the past decade. A number of nonhematopoietic sources of stem cells (or progenitor cells) have been identified, including endothelial stem cells and neural stem cells. These discoveries have been a major step toward the use of stem cells for potential clinical applications of organ regeneration. Accordingly, kidney regeneration is currently gaining considerable attention to replace kidney dialysis as the ultimate therapeutic strategy for renal failure. However, due to anatomic complications, the kidney is believed to be the hardest organ to regenerate; it is virtually impossible to imagine such a complicated organ being completely rebuilt from pluripotent stem cells by gene or chemical manipulation. Nevertheless, several groups are taking on this big challenge. In this manuscript, current advances in renal stem cell research are reviewed and their usefulness for kidney regeneration discussed. We also reviewed the current knowledge of the emerging field of renal stem cell biology.